Informing research participants of research results: analysis of Canadian university based research ethics board policies - MacNeil, S D (BMJ Group, 2006)
BACKGROUND: Despite potential benefits of the return of research results to research participants, the TriCouncil Policy Statement (TCPS), which reflects Canadian regulatory ethical requirements, does not require this. The policies of Canadian research ethics boards (REBs) are unknown. OBJECTIVES: To examine the policies of Canadian university based REBs regarding returning results to research participants, and to ascertain if the presence/absence of a policy may be influenced by REB member composition. DESIGN: Email survey of the coordinators of Canadian university based REBs to determine the presence/absence of a policy on return of research results to research participants both during an ongoing study and at conclusion. REB coordinators were asked to return a copy of the policy or guidelines and to describe the member composition of their REB. FINDINGS: Of 50 REBs that were contacted 34 (68%) responded and 22 (64.7%) met the inclusion criteria. Two (9.1%) had a policy that governed the return of research results while on a study, and seven (31.8%) following the completion of a study. Presence of an ethicist or a lawyer on the REB did not influence the presence/absence of such policies. No REBs had specific guidelines describing how participants should be informed of results. CONCLUSIONS: Most REBs did not require researchers to disclose study results to research participants either during or following a study. Thus this study identifies an ethical shortcoming in the conduct of human research in Canada. It has also demonstrated that there are no clear recommendations by REBs to facilitate the return of results to participants following research projects.